The Lived Experience of Involuntary Childless in Indonesia: Phenomenological Analysis - Miwa Patnani; Bagus Takwin; Winarini Wilman Mansoer (Universitas Ahmad Dahlan, 2020)
The absence of children in marriage has some impact on the couple. Empirical studies showed a different result, one is that it brings out a positive impact, and another says the other side. This discrepancy leads to the question of what causes that contradictive finding. This study is aimed to explore the lived experience of involuntary childlessness and determine the context of that experience. In order to get the whole understanding of the experience, this study is using the depth interview method with a phenomenological principle. Participants of this study are 11 involuntary childless who have married for at least 3 years. Results show 8 themes that describe the experience of involuntary childlessness, including positive and negative experience, acceptance, spousal, social and spiritual relationship, conflict, and marital evaluation. The context that determines the experience is the relationship with the spouse, family, community, and the spiritual matter of the couple.